Principles, methods and modern trends in analysis of residential real estate market - Булаенко, Диана Владимировна (Technology audit and production reserves, 2014)
This article provides an overview of existing approaches and methods to analysis and forecasting of the residential real estate market as well as the problem of development of a multifactorial mathematical model of the price per square meter of residential real estate in the city of Kharkov. It also analyzes the current state of the subject area and reveals that one of the acute issues of analyzing real estate market data lies in the automated search of the key factors that determine the behavior of the system, and as a whole there is a need for automation of the process of analyzing and processing the results of measurements to construct mathematical models. The main purpose of the research is to develop an automated method of structural identification of multivariate model to predict property prices and increase efficiency of the resulting model. Development of an automated method of structural identification of a multifactional model of the price in the residential real estate market facilitates the adoption of scientifically substantiated practical solutions in management and study of both the development of this market and the economy as a whole. This model will allow to model values of price indicators based on the different possible scenarios in the economy considering economic situation of the city and the country. The results of the research can be used in the purchase and rental transactions, in cadastral valuation of residential real estate for taxation purposes, in development of projects and other dealings with residential real estate.